Influence of scandium interlayer on the mechanical and metallurgical characteristics of friction stir welded AA1200-H14/ Sc/AA6061-T6 - D Arunkumar; K S Vijay Sekar (Materials Research Express, 2024)
The present investigation observed the friction stir welding (FSW) of joints made from the interfacial layered dissimilar AA1200-H14 and AA6061-T6 using scandium about the UTS, frictional heat, and metallurgical properties. The experimental examination is carried out utilising a three-level, three factors, Box-Behnken Design matrix (17 tests) in response surface approach, with the welding speed (WS), axial force (AF), and tool rotation speed (TRS) as the stated input parameters. Analysis of variance (ANOVA) was used to evaluate the model’s dependability. Macroscopic and microscopic joint defects, as well as the alloy intermixture, have been found using optical microscopy and SEM. The SEM microstructural study exhibited that the generated grains are fine and equiaxed. The optimal WS (50 mm min ^−1 ), A ^−1 F ^−1 (10 kN) and TRS (1750 rpm) settings produced the maximum terminal tensile strength (200.182 MPa) and perfect frictional heat observations. The inclusion of scandium interlayer as well as optimised parameters improved the joint’s mechanical characteristics and produced a fine-grained microstructure.